(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In Mongolia, the ethnoecological views of the Uzbeks of the Fergana Valley with livestock were briefly analyzed based on scientific sources and ethnographic field inscriptions. Scientific conclusions on the ethnoecological views of Uzbeks in the Fergana Valley with livestock are presented in Magana.